MANCHESTER DECODER WITH HIGH ROBUSTNESS - Lovrekovic, Zoran (Journal of process management and new technologies, 2019)
There are some diferent principles for realisation of the Decoder of the Manchester signal: -Decoder developed with the active filters, decoder based on the oscilator with codin signal controled frequency of clock, and decoder with PLL circuit, are the usual way for the realisation of that device. The suggested realisation of the decoder of Manchester signal is very robust, which is seen in the possibility, opposite to other types of Manchester decoders, to work properly even if the signal interval of the input signal vary up to ± 25%, and in a very simplified realisation.